Comparison of Shearwave Elastography and Apri Score for Liver Fibrosis in Patients of Chronic Liver Disease - Deedar Hussain, Israr-Ul-Haque, Ghias-Ul-Hassan, Khurram Malik, Shafqat Rasool, Ghias-Un-Nabi-Tayyab, (Pakistan Journal of Medical & Health Sciences, 2022)
Chronic liver disease of various etiologies is the major causes of mortality and morbidity globally. Liver biopsy is the most accurate and oldest method to determine the chronic liver disease progression and for liver histology. Shear wave elastography (SWE) is a new non-invasive technique that applies localized mechanical compression to the soft tissue with focused ultrasonography and obtains tension images showing the tissue response. Aspartate aminotransferase to platelets ratio (APRI) on the other hand is relatively less expensive test and can be done on outpatient basis. Objective: To find the relation between APRI aspartate and SWE for detection of liver fibrosis in patients with chronic liver disease. Study Design: A Cross Sectional study Setting: Medical Unit-1 Lahore General Hospital Lahore and Department of Gastroenterology & Hepatology, Doctors Hospital and Medical Centre, Lahore. Study Duration: From July 2019 to December 2021. Methods: 180 patients met the criteria of inclusion were included, the blood samples were obtained and sent to the hospital laboratory for valuation of AST and Platelets. Reports were evaluated, APRI was calculated and patients were labeled as negative or positive. Then all patients underwent SWE by a senior radiologist for assessment of liver fibrosis. Patients were labeled as negative or positive. Agreement was noted, all data was entered on a specifically designed proforma, and data were analyzed and entered in SPSS version 20 statistical method. Agreement was calculated by generating 2x2 tables between APRI and SWE findings. Kappa statistics was calculated to measure the strength and significance of agreement. P-value ≤0.05 was taken as significant. Results: In this study, the patients mean age was 46.39 ± 16.02years. There were 119 (66.11%) males and 61 (33.89%) females. The mean BMI of patients was 24.70 ± 5.23kg/m2. The mean duration of CLD was 5.50 ± 2.672 years. The mean AST of patients was 73.98 ± 60.23IU/L while mean platelet count was 200.65 ± 92.47/cm3. The mean APRI was 1.41 ± 1.20. The mean SWE was 18.32 ± 23.85kPa. The APRI and SWE agreed on 73 (54.9%) cases and showed 66.7% agreement between them for diagnosis of liver fibrosis (p<0.05). Conclusion: Thus, APRI and SWE showed strong agreement but further trials are required to confirm the evidence. Keywords: Agreement, APRI, Aspartate aminotransferase to platelets ratio, SWE, Shear-wave elastography, Chronic liver disease and Liver fibrosis.